2020
DOI: 10.1161/strokeaha.119.027749
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Etiology and Thrombus Computed Tomography Characteristics in Patients With Acute Ischemic Stroke

Abstract: Background and Purpose— If a relationship between stroke etiology and thrombus computed tomography characteristics exists, assessing these characteristics in clinical practice could serve as a useful additional diagnostic tool for the identification of stroke subtype. Our purpose was to study the association of stroke etiology and thrombus computed tomography characteristics in patients with acute ischemic stroke due to a large vessel occlusion. Methods— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
4
40
0
1
Order By: Relevance
“…This result is in line with a recent computed tomography (CT) study conducted in ischemic stroke patients before MT that reported lower thrombus length in CE subtypes compared to non‐CE subtypes. [21] The higher rate of spontaneous thrombus lysis previously observed in CE compared to LAA subtypes may account for our finding. [22] However, it is unclear whether the thrombus length comes from a single proximal source (CE, LAA) or reflects an additional thrombus extension due to low flow effects on coagulation and thrombosis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This result is in line with a recent computed tomography (CT) study conducted in ischemic stroke patients before MT that reported lower thrombus length in CE subtypes compared to non‐CE subtypes. [21] The higher rate of spontaneous thrombus lysis previously observed in CE compared to LAA subtypes may account for our finding. [22] However, it is unclear whether the thrombus length comes from a single proximal source (CE, LAA) or reflects an additional thrombus extension due to low flow effects on coagulation and thrombosis.…”
Section: Discussionmentioning
confidence: 58%
“…These results are in line with previous studies showing similar histological and CT thrombus features in strokes of undetermined etiology (UDE) and CE subtypes. [21,30] Thus, it may be worthwhile in further studies to investigate how the use of SVS length and MMP‐9 level may help to manage etiological workup, especially optimal duration of cardiac monitoring in patients with large vessel ESUS, although atrial fibrillation is not the only potential CE source in these patients. [31] Given the burden of stroke, this issue involved not only stroke specialists but all neurologists.…”
Section: Discussionmentioning
confidence: 99%
“…A recent subgroup analysis from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) Registry has confirmed that thrombus computed tomography characteristics of cardioembolic (CE) stroke are distinct from those of non-CE stroke. Non-CE strokes were associated with the presence of hyperdense artery sign, a higher clot burden, a shift towards a more proximal thrombus location, and longer thrombi compared with a CE cause [1]. The differences in imaging characteristics between stroke etiologies are likely a result of differences in the composition of the occlusive thrombus resulting from dissimilarities in the clotting mechanisms.…”
Section: Introductionmentioning
confidence: 96%
“…According to the American Heart Association, 87% of all strokes are ischemic [ 82 ], caused mainly by the obstruction of major cerebral arteries, especially the middle cerebral artery (MCA) or its branches [ 83 ]. Typically, the study of ischemic stroke in rodent models has focused in the MCA territory [ 84 ].…”
Section: Interventions To Induce Ischemic Strokes In Pigsmentioning
confidence: 99%